Analisis Sentimen Citayam Fashion Week pada Komentar YouTube dengan Metode Convolutional Neural Network - George Alexander Suwito; Imam Cholissodin; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Citayam Fashion Week's virality started with the circulation of interview videos on Tiktok and Instagram. The positive impact was felt especially for traders due to the high number of visitors who wanted to see the event so that they could increase their turnover, apart from the positive impact felt, traffic jams arise due to the high number of visitors and the location of the fashion show action, thereby disrupting the activities of the general public. Citayam Fashion Week was disbanded on Wednesday, 27 July 2022. This caused debate among the public. Some people support the holding of the event, some people do not support holding the event. Various positive, and negative comments were given by the public to the Citayam Fashion Week event, therefore a method is needed that can automatically sort out user sentiments. and efficiently, avoiding public misperceptions of existing comments. In this study the authors used the Convolutional Neural Network (CNN) method in conducting sentiment analysis, based on the results of the tests that have been carried out, this system has the best metric evaluation value, namely an accuracy value of 97%, a precision value of 97%, a recall value of 98%, and the f-measure value of 97%.